THE SPECTRUM OF INTERNAL FRICTION IN THE Se - A. N. Kabanskayа; V. A. Lomovskoy; A. A. Gorshkov; Z. I. Fomkina; E. V. Kopylova (Тонкие химические технологии, 2013)
Dissipation in selenium was investigated using internal friction spectrum for the temperature range -150–250°C and the frequency domain 0.1–10 Hz. It was found that only the use of a combined specimen with isinglass stone undercoat allows the tests of selenium in the mentioned temperature range. For unannealed selenium four local dissipation peaks of the internal friction spectrum were observed in the temperature range -130÷+225°C. Two peaks (α and ) are relaxation peaks, and two others ( c  and С) are nonrelaxation peaks. All observed dissipation peaks of the internal friction spectrum were interpreted on the basis of calorimetric tests results. It was also found that the thermal treatment of selenium results in the annihilation of the α-relaxation peak and strong decrease of the dissipative process С.